A new electrochemical sensor based on carbon paste electrode/Ru(III) complex for determination of nitrite: Electrochemical impedance and cyclic voltammetry measurements. (October 2016) - Terbouche, Achour; Lameche, Siham; Ait-Ramdane-Terbouche, Chafia; Guerniche, Djamila; Lerari, Djahida; Bachari, Khaldoun; Hauchard, Didier
Graphical abstract: Highlights: Modified CPE/Ru(III) complex electrode was used as sensor for the determination of nitrite. The behavior of nitrite on the surface of modified electrode was investigated. Electrochemical impedance and cyclic voltammetry measurements were performed. The charge transfer resistance decreased with increasing potentials and temperature. The sensor exhibited a wide linear range for nitrite detection from 0 to 0.0138 M. Abstract: The modified carbon paste electrode with Ru(III) complex was studied as a novel sensor for the determination of nitrite. The behavior of NO2 − at the electrode surface was investigated using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). EIS provided useful information on the charge transfer resistance ( R ) at the electrode/solution. The EIS measurements showed that R is low at oxidation potentials, and decreases with increasing temperature. The increase of the constant phase element with temperature is due to the accumulation of nitrite on the electrode, thus, facilitating the electron transfer between electrode and NO2 − . CV was used to study the effect of pH on the electro-catalytic oxidation of NO2 − and to determine the limit of detection (LOD). CV measurements showed a good linear relationship between the oxidation current and the concentration of NO2 − over a wide concentration range 0–1.38 × 10 −2 mol L −1 . Low detection limit of 1.39 × 10 −6 mol L −1 toward NO2 − was obtained. LOD decreased by 23.2% compared to that determined using cavity microelectrode.